[PP.27.12] VISCERAL ADIPOSITY INDEX IS ASSOCIATED WITH NOCTURNAL HYPERTENSION BUT NOT NON-DIPPING PATTERN IN UNTREATED HYPERTENSIVE PATIENTS. (September 2016) - Manousopoulos, K.; Manios, E.; Chouzouri, V.; Michas, F.; Lykka, A.; Papageorgiou, C.; Vettou, C.; Zakopoulos, N.
Abstract : Objective: The visceral adiposity index (VAI) is a sex-specific scoring system that can be used as a marker for both visceral fat dysfunction and individual's subsequent cardiometabolic risk. A recent study demonstrated that a higher VAI was associated with arterial hypertension. However, it remains unclear whether non-dipping status or nocturnal hypertension is associated with VAI. Aim of our study was to evaluate the impact of non-dipping status and nocturnal hypertension on VAI in untreated hypertensive patients. Design and method: A total of 176 consecutive never treated subjects referred for evaluation to the Hypertension Unit of our department, underwent 24-h ambulatory BP monitoring and biochemical blood tests. The VAI was calculated as follows: for male (waist/(39.68+(1.88*BMI)))*(Tg/1.03)*(1.31/HDL) and female (waist/(36.58+(1.89*BMI))) *(Tg/0.81)*(1.52/HDL). The degree of nocturnal systolic BP (SBP) dipping (%) was calculated as 100[1 – nighttime SBP/daytime SBP]. Dippers were defined as subjects with nocturnal SBP fall >10% and non-dippers as patients with nocturnal SBP fall <10%. Nocturnal hypertension was defined as nighttime SBP > = 120 mmHg or DBP > = 70 mmHg. Statistical analysis was performed by means of independent-samples T test, x-square and ANCOVA. Results: The study population consisted of 176 subjects with mean age (54y ± 10). The percentage of patients with nocturnal hypertension was 62%, whereas the percentage of non-dippers was 35%. VAI did not differ significantly between non-dippers (3.97) and dippers (3.88). In contrast, patients with nocturnal hypertension presented significantly (p = 0.012) higher VAI (4.31) than patients with nocturnal normotension (3.26), even after adjustment for demographic characteristics and baseline risk factors. Conclusions: A higher VAI was associated with nocturnal hypertension but not non-dipping pattern in untreated hypertensive patients.